The patrimony mining metallurgist of Tinyahuarco - Guadalupe, Enrique (2006)
The Metallurgical Mining Patrimony of Tinyahuarco (Smelter) is located 10 km southwest of Cerro de Pasco city, and between years 1906 and 1923, was the biggest foundry of the time that worked. The remains of the foundry deserve to be catalogued as a metallurgical mining patrimony because besides the infrastructure of walls and columns, which persist until today, also remain some parts like the furnace, the coke plant, some offices and the hotel; from them, the one that is in good condition, is the superintendent residence, which at the moment is inhabited. It is important to remark the history of the mining activity in this region that was transformed by the presence of the foundry of Tinyahuarco (Smelter), constructed with North American investments that helped to develop the mining industry with the best technology of the time, changing many social and economical aspects of the region and therefore of the country. The given value of the mining patrimony of Tinyahuarco is of great importance for the zone, because it is necessary to be prepare before the mine closing, for what, areas for sustainable development must be created, which implies to take advantage of the mining and metallurgical aspects and other attractiveness of the zone; so that, these patrimonies serve with educational aims, research, recreational and tourism; the last one could generate economical flow and it is possible to create natural attractive touristic circuits and cultural ones, which exist in the zone and is necessary to be studied and evaluated.